A theory on the performance of reinforced-concrete elements. Issue 1 (20th February 2019) - Kar, Anil K.
Abstract : It has always been assumed that the bond between concrete and rebars, whether plain or ribbed, provides adequate engagement for the desired performance of reinforced-concrete elements. However, it is conceivable that the surface conditions of rebars could influence this performance. Tests have revealed that the performance, whether of flexural or compression elements, depends on surface conditions as well as on the configurations of rebars. It is theorised that besides depending on the strengths, dimensions and areas of concrete and rebars, the performance of reinforced-concrete elements is also influenced by the levels of effective bond or engagement between rebars and their surrounding concrete. This engagement can be governed, besides the properties of concrete, by the coupled effects of hardness and texture of the rebar surface, surface features and the configuration of rebars along their length. This knowledge has an added advantage in the design of concrete structures.